Identifikasi Budaya Makan dan Pengetahuan Ibu Selama Kehamilan Dengan Kejadian Stunting Pada Anak - Simamora, Marthalena; Annisa; Taruli Rohana Sinaga; Rani Kawati Damanik (Universitas Sari Mutiara Indonesia, 2024)
Stunting also known as stunted, is a condition of failure to grow in children due to chronic malnutrition and recurrent infections, especially during pregnancy. One of the factors for the high incidence of stunting in children is a lack of maternal knowledge. Cultural influences greatly determine the health status of children where there is a direct link between culture and knowledge. The Purpose of this research is to identification of eating culture in society and mother's knowledge during pregnancy on stunting children in the Working Area of the Bebesen Health Center, Central Aceh District. This study uses mixed method, quantitative with cross sectional design and qualitative with phenomenological design. Sampling used a purposive sampling technique with a population of 210 people with a sample size of 62 people with quantitative details of 62 people and qualitative details of 5 people with inclusion criteria. Data collection quantitative instruments used questionnaires and for qualitative used voice recorders as well as interview guides. Data analyzed using Chi square test and the N-vivo Version 12. The results of the quantitative reasearch is showed that there was a significant relationship between knowledge and the incidence of stunting in toddlers with a p value of 0.001. qualitative research obtained 4 themes, namely 1.) cultural practices carried out; 2.) trousers during pregnancy; 3.) habits during pregnancy; 4.) the impact of the restrictions implemented. The conlusion for quantitative is the better knowledge the smaller the incidence of stunting and For qualitative was found that there are several food cultures and taboos that exist in culture society.